Morphology and Morphometry of the Lung in Corn Snakes (Pantherophis guttatus) Infected with Three Different Strains of Ferlavirus. Issue 4 (May 2017) - Starck, J.M.; Neul, A.; Schmidt, V.; Kolb, T.; Franz-Guess, S.; Balcecean, D.; Pees, M.
Summary: Ophidian paramyxovirus (ferlavirus) is a global threat to reptilian sauropsids in herpetological collections, with occasional but fatal effects. This study characterizes the effects of three different genetic strains of ferlavirus on the dynamic changes of histology and morphometry of the lung of corn snakes ( Pantherophis guttatus ). Lungs from 42 corn snakes were either sham-infected or infected experimentally under standardized conditions. From 4 to 49 days after intratracheal inoculation, the lungs were examined qualitatively and quantitatively. Progressive microscopical changes were seen in the lung. Initially, increased numbers of heterophils were observed in the interstitium followed by proliferation and vacuolation of epithelial cells lining faveoli. Electron microscopy revealed loss of type-I pneumocytes, hyperplasia of type-II pneumocytes, and interstitial infiltrates of heterophils and mononuclear cells. With progression of disease the respiratory epithelium was initially overgrown by transformed type-II pneumocytes and later became multilayered. The results of the study suggest that the respiratory capacity of the lungs declines with disease development. The dynamics of disease development and histopathology differed in snakes infected with different ferlavirus genogroups. Animals infected with virus genogroup B developed histopathological changes and morphometric changes more rapidly and of greater intensity than snakes infected with viruses from genogroups A or C.